Phenomenology of A Paggadde-Gadde’s Resilience in Managing Their Business Post-Quarantine of Covid-19 Period - Dien Triana; Andi Sri Wahyuni; Rizky Utami (International Journal of Religious and Cultural Studies, 2022)
The covid-19 pandemic has changed the lives of economic agents, making survival a critical issue and attention to small businesses sectors is crucial because they lack savings for survival. For example, Mama Aris was a gadde-gadde businesswoman who survived the pandemic and financial issues after her husband retired. Therefore, this study aimed to unravel Mama Aris’s resilience as a paggadde-gadde in managing her business finances during the pandemic. Using phenomenology methodology, the study showed toughness from speech, tears, voice intonation, and body language of informants while telling their stories. The triangulation technique was used in order to obtain accurate data. The results showed that the tears and words of paggadde-gadde were caused by the financial difficulties and life during the pandemic in the isoman period. However, mama Aris had hopes again when talking about diversifying products. gadde-gadde’s income was turned into capital for making new products orders by the management. Moreover, there was an additional capital for gadde-gadde supplies. Mama Aris gained knowledge that was used as a new finding in small and medium enterprise study. This had important implications in solving small business actors with financial difficulties in the future.